Article Review: Pharmacological Activities of Renggak Plant (Amomum dealbatum Roxb.) - Cahyani, Dina Fathia; Hidayati, Agriana Rosmalina (Jurnal Biologi Tropis, 2024)
The renggak plant (Amomum dealbatum Roxb.) is a native plant of Lombok Island that belongs to the Zingiberaceae family and is traditionally used as a remedy for coughs, diarrhea, arthritis, and eye washes. Ethanol extract from the renggak fruit is reported to contain secondary metabolites such as flavonoids, tannins, terpenoids, alkaloids, steroids, saponins, polyphenols, and several other types of fatty acids, which have various pharmacological activities. This review article aims to provide information on the various pharmacological activities of the renggak plant, including antidiabetic, antiurease, antioxidant, antibacterial, and antifungal activities. The method used in this article is a systematic review of various literature sources. Articles were collected using the Google Scholar and PubMed databases with keywords such as Renggak, Amomum dealbatum Roxb., and pharmacological activities. Based on the data results, it can be concluded that the renggak plant (Amomum dealbatum Roxb.) exhibits pharmacological activities as an antidiabetic, antiurease, antibacterial, antioxidant, and antifungal agent.